1986
DOI: 10.1051/rnd:19860428
|View full text |Cite
|
Sign up to set email alerts
|

Newborn calf intestinal absorption of immunoglobulins extracted from colostrum

Abstract: Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
3
16
1
Order By: Relevance
“…No significant drop was recorded in the animals fed bovine colostrum, which indicate that the energy supply of such a diet was correct. The hematocrit (Table 4) was generally decreasing with time, which is in agreement with Grongnet (1986). Even if it is rare, rapid anaemia is always to be feared when newborn lambs receive bovine colostrum (Winter, 1983;Bernadina and Franken, 1985).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…No significant drop was recorded in the animals fed bovine colostrum, which indicate that the energy supply of such a diet was correct. The hematocrit (Table 4) was generally decreasing with time, which is in agreement with Grongnet (1986). Even if it is rare, rapid anaemia is always to be feared when newborn lambs receive bovine colostrum (Winter, 1983;Bernadina and Franken, 1985).…”
Section: Resultssupporting
confidence: 67%
“…On the other hand, destruction of indifferent germs is not needed for good intestinal transfer since, in the case of this experiment, no difference between native and heat treated colostrum was found as far as IgG plasma levels are concerned. If mixed and thawed colostrum or dried colostrum products (for instance semi-purified immunoglobulin) are characterized by low intestinal transfer (Grongnet et al 1986(Grongnet et al , 1995, the reason cannot be normal flora even if it is superabundant. Destruction or removal during processing of a specific absorption factor should be further taken into consideration.…”
Section: Resultsmentioning
confidence: 99%
“…Balfour and Comline (1962) showed that Ig added to a saline solution were very poorly absorbed, this has been confirmed by Grongnet et al (1986). Therefore the key to efficient absorption of Ig appears to be in the colostrum itself.…”
Section: Diet Compositionmentioning
confidence: 61%
“…Therefore, it would be necessary to semi-purify the colostrum, however, this leads to the production of a colostrum for which the Ig are absorbed less efficiently. After this type of treatment, which may eliminate the factor thought to help absorption by Balfour and Comline (1962), the absorption of the Ig can be very low (Grongnet et al, 1986(Grongnet et al, , 1996. This was not the case for Nousiainen et al (1994) and more recently Grongnet et al (unpublished results) who showed that absorption and blood Ig levels were sufficient to give protection.…”
Section: The Role Of the Farmer And Industrymentioning
confidence: 99%
“…Another option would consist in the removal of most of the fat and protein of the colostrum. Extraction of immunoglobulins from colostrum, followed by their concentration may be used but according to Grongnet et al [20], such extracted immunoglobulins are poorly absorbed by the intestine of the newborn calf. Some food additives which might help reestablish the absorption capacity have been tested by the same authors (Grongnet et al [19]).…”
Section: Introductionmentioning
confidence: 99%